1999
DOI: 10.1164/ajrccm.160.4.9807120
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of IL-12 Receptor mRNA in Active Pulmonary Tuberculosis and Sarcoidosis

Abstract: Cytokines have been implicated in the pathophysiology and development of pulmonary diseases such as tuberculosis and sarcoidosis. In particular, the numbers of cells expressing Th1-type cytokines such as IFN-gamma and IL-12 are increased within the lungs of patients with these granulomatous diseases. As a factor promoting the commitment of naive lymphocytes to a Th1-type profile of cytokine expression, IL-12 may be pivotal in the cascade of proinflammatory events within the airways. In this study, we examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 29 publications
2
32
1
1
Order By: Relevance
“…The interaction of CD40 and CD40 ligand may be a clue to the greater induction of IL-12 p70 in sarcoid BAL fluid cells than in normal BAL fluid cells. BAL fluid T cells in sarcoid cases showed enhanced expression of IL-12␤ 2 R (22) and most BAL fluid T cells differentiated into Th1 (or T cytotoxic 1) cells (24). The expression of IL-18R was also up-regulated in Th1 cells (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of CD40 and CD40 ligand may be a clue to the greater induction of IL-12 p70 in sarcoid BAL fluid cells than in normal BAL fluid cells. BAL fluid T cells in sarcoid cases showed enhanced expression of IL-12␤ 2 R (22) and most BAL fluid T cells differentiated into Th1 (or T cytotoxic 1) cells (24). The expression of IL-18R was also up-regulated in Th1 cells (35).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of recent Th1 and Th2 paradigms, the cytokine profile of sarcoidosis is Th1 dominant when disease activity is high (17)(18)(19). Recent studies have demonstrated enhanced expression of IL-12 (20 -22) and IL-12R (23,24) in sarcoid lungs. IL-18 expression was reported to be increased in the airway epithelial cells of sarcoid cases (25).…”
mentioning
confidence: 99%
“…Individuals with mutations in the IL-12R genes have increased susceptibility to infection by Mycobacteria and Salmonella (30,31). In studying patients with tuberculosis and sarcoidosis, lung T cells were found to express high levels of IL-12R␤2 in comparison to normal controlled subjects (32). Yet there is a recent report of an IL-12R␤1-independent pathway of IL-12 responsiveness in human T cells (33).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, alveolar macrophages from patients with sarcoidosis have been shown to produce interleukin (IL)-12 in addition to TNF-a, IL-1b, and IL-6 [20][21][22][23][24][25][26][27][28][29]. Overexpression of IL-12, by activated alveolar macrophages, results in enhanced Th-1 cell proliferation and activation, leading to the increased expression of the pro-inflammatory mediators IFN-c and TNF-a, and the secretion of cytokines and chemotactic factors that could, in turn, recruit and activate additional T-cells.…”
Section: Introductionmentioning
confidence: 99%